Configuration and connectivity of green areas: a method for sustainable urban growth planning - Pereira, Edilson (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective: develop a method to identify and analyze green areas in Blumenau (SC), assessing their connectivity and integration within the context of sustainable urban planning. Methodology: satellite images (NDVI > 0.60) were used, combined with Space Syntax and the Voronoi Diagram in a GIS environment (QGis) to map vegetation and urban fragments. Originality/relevance: this study contributes to the integration of geometric and syntactic tools in the analysis of green area connectivity, promoting more sustainable urban planning. Results: the analyses revealed a lack of high-quality vegetation near water resources, affecting biodiversity. Regions with high integration potential were also identified, suggesting ecological corridors and priority areas for preservation or reforestation. Theoretical/methodological contributions: the proposed method can be replicated in other urban contexts, assisting in environmental diagnostics and green infrastructure strategies. Social and environmental contributions: the study reinforces the importance of nature-based solutions in urban planning, fostering more resilient, biodiverse, and sustainable cities.